En ordboksfamilj med anor. Om en lång och obruten tradition i engelsk-svensk och svensk-engelsk lexikografi - Olufsson, Arne (LexicoNordica, 2004)
The present scene in bilingual lexicography for English and Swedish is dominated by the Norstedt ”family” of dictionaries. All sizes are represented, from the top pair, where each member features 135,000 ”words and phrases”, down to the phrase-book format. The aim of this article is to describe the historical network behind the Norstedt works on the market today. It is demonstrated that for the production of this publishing-house and its immediate predecessors (Svenska Bokförlaget and Esselte Studium), there is no real break in the English-Swedish tradition between 1889 and 2000 and none in the Swedish-English one between 1904 and 2000. Particular attention is paid to the older dictionaries, their microstructure and the vacillation as to their intended function in terms of reception and production.